Use of Pentoxypline and Tocopherol in the treatment of Osteorradionecrosis: a literature review - Gusmão , Jonas Nogueira Ferreira Maciel; Gomes Júnior , George Matos Ferreira; Rêgo, Roberto Dias; Santos , Eliardo Silveira (Brazilian Journal of Case Reports, 2021)
Osteoradionecrosis (ORN) is a complication of radiotherapy (RT), which affects patients with head and neck cancer. Once established, an ORN does not disappear spontaneously and a standard treatment has not yet been defined. Treatment is often complex and multimodal. With a better understanding of the pathophysiology of ORN, new treatments and possibilities for the most predictable results of this difficult prognosis pathology arise. Under these circumstances, good results have been observed with an association of peripheral vasodilator drugs and antioxidants, such as pentoxifylline and tocopherol. The objective of this work was, through a review of the literature, to describe a pathophysiology of the ORN of the jaws and discuss as new perspectives of a conservative treatment with pentoxifylline and tocopherol. It was observed as an alternative to the drug association as a therapeutic alternative of the ORN, mainly in the early stages, it showed good results; However, it requires more controlled clinical studies to measure and consolidate the benefits that this treatment can provide patients.